2014
DOI: 10.1371/journal.pone.0099686
|View full text |Cite
|
Sign up to set email alerts
|

Heading for the Hills: Risk Avoidance Drives Den Site Selection in African Wild Dogs

Abstract: Compared to their main competitors, African wild dogs (Lycaon pictus) have inferior competitive abilities and interspecific competition is a serious fitness-limiting factor. Lions (Panthera leo) are the dominant large carnivore in African savannah ecosystems and wild dogs avoid them both spatially and temporally. Wild dog young are particularly vulnerable and suffer high rates of mortality from lions. Since lions do not utilize all parts of the landscape with an equal intensity, spatial variation in lion densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Den sites are an important aspect of many mammalian species' ecology, and risk avoidance (e.g., anthropogenic, conspecific, predation) has been found to influence den site selection of several carnivore species (Theuerkauf et al 2003, Libal et al 2011, Jackson et al 2014. We found that black bears appeared to minimize anthropogenic risk during denning; however, females with cubs must also balance the increased energetic demands of rearing young while minimizing their mortality risk.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Den sites are an important aspect of many mammalian species' ecology, and risk avoidance (e.g., anthropogenic, conspecific, predation) has been found to influence den site selection of several carnivore species (Theuerkauf et al 2003, Libal et al 2011, Jackson et al 2014. We found that black bears appeared to minimize anthropogenic risk during denning; however, females with cubs must also balance the increased energetic demands of rearing young while minimizing their mortality risk.…”
Section: Discussionmentioning
confidence: 74%
“…, Jackson et al. ). We found that black bears appeared to minimize anthropogenic risk during denning; however, females with cubs must also balance the increased energetic demands of rearing young while minimizing their mortality risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lions and hyaenas respond to this resource variability and, as the dominant apex carnivores, select the most resource‐rich habitats, avoiding rugged areas, for instance, in favor of prey‐rich flatter terrain (Mills & Gorman, ). The resulting spatial variability in lion and hyaena densities facilitates avoidance by subordinate wild dogs (Mills & Gorman, ) and the development of a landscape of fear where high‐risk habitats are avoided and competition refuges are actively selected, particularly during the vulnerable denning season when rugged and densely vegetated areas, with fewer lions, are selected by wild dogs (Davies, Marneweck, Druce, & Asner, ; Jackson et al, ). Indeed, fluctuations in lion densities have been shown to elicit changes in wild dog behavior and habitat selection (Groom et al, ).…”
Section: Discussionmentioning
confidence: 99%